Be honest and tell the truth - Meiners, Cheri J., 1957-; Johnson, Meredith (Minneapolis, MN : Free Spirit, 2007)
Teaches young readers the importance of telling the truth and reassures them that, even though it may be difficult, it is always best to be honest. Includes discussion questions, games, and activities.
2.2
K-3
K-3
Keywords: Honesty -- Juvenile literature; Honesty; Honesty